2016
DOI: 10.1089/hum.2015.159
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Neuritin Promotes Nerve Regeneration After Acute Spinal Cord Injury in Rats

Abstract: Insufficient local levels of neurotrophic factor after spinal cord injury (SCI) are the leading cause of secondary injury and limited axonal regeneration. Neuritin belongs to a family of neurotrophic factors that promote neurite outgrowth, maintain neuronal survival, and provide a favorable microenvironment for the regeneration and repair of nerve cells after injury. However, it is not known whether the exogenously applied neuritin protein has a positive effect on nerve repair after SCI. This was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Neuritin overexpression induces the recovery of crushed optic nerve in mouse (Sharma et al, 2015). We recently showed that recombinant Neuritin protects neurons against apoptosis following spinal cord injury (Gao et al, 2016). In the present study, we investigated whether Neuritin can restore nerve structure and function in a rat model of sciatic nerve injury.…”
Section: Introductionmentioning
confidence: 99%
“…Neuritin overexpression induces the recovery of crushed optic nerve in mouse (Sharma et al, 2015). We recently showed that recombinant Neuritin protects neurons against apoptosis following spinal cord injury (Gao et al, 2016). In the present study, we investigated whether Neuritin can restore nerve structure and function in a rat model of sciatic nerve injury.…”
Section: Introductionmentioning
confidence: 99%
“…where they suggested that neuritin created an environment that promoted nerve cell survival and neurite regeneration after SCI, thus contributing to nerve regeneration and recovery of motor function [27] . Besides spinal cord injury, results obtained by Zhao et al suggest that soluble neuritin secreted by astrocytes promoted the recovery of injured hippocampal neurons via adherance to the surface of neurons in ischemic brains [28] .…”
Section: Neuritin Promotes Neuritogenesis and Neuronal Regenerationmentioning
confidence: 99%
“…Neuritin promotes neurite growth and synaptogenesis in hippocampal and cortical neurons (4,5), and is related to the recovery from nerve injury and learning memory (6)(7)(8). It has further been found that recombinant Neuritin (9) improves nerve regeneration following acute spinal cord injury (10) and sciatic nerve injury in rats (11).…”
Section: Introductionmentioning
confidence: 99%